Nilai Pendidikan dalam Konsep Rumah Islami - Ahadi, Maulana; Nurul Huda (STAI Kuala Kapuas, 2024)
The background of this research is the lack of attention to aspects of Shari'a in building houses and the lack of ability of the head of the family to provide a decent place to live for his children and wife, having many children certainly has a big challenge in the introduction of Islamic education at home. Activities that are private mixed beds between boys and girls who are baliqh, and other activities will certainly have an impact on the psychology of children's education. The research aims to explore theories of Islamic education and health sciences related to housing that are by Islamic concepts. This research is based on a qualitative approach with qualitative descriptive analysis based on secondary data in Islamic education theories, as well as taken from various studies, literature and previous studies. From this research, it is known that the home is a very important place to instill Islamic education.